The Impact of Disclosure of Related Parties in the Auditor’s Report and its Reflection on Enhancing Investment Decisions - Muna Jabbar Mohammed (Technium Business and Management, 2024)
The research aims to investigate the importance of disclosing related party transactions in the auditor’s report, and to explain the nature of the misstatements involved in related party transactions according to professional publications. In addition to showing the impact of disclosure of related parties in the auditor’s report to enhance the investment decisions of users of those statements, and to achieve the research aims , the inductive method was relied upon as well as the deductive analytical method was used to reach the research objectives. The study tool was used, which was represented in a questionnaire for all Data from the research sample, as the questionnaire was distributed to a number of sample members, and the number was appropriate for conducting statistical analysis as it reached 50 questionnaires, of which 48 questionnaires were suitable for analysis through the Statistical Package for the Social Sciences (SPSS) program. After analyzing the study variables and testing the hypothesis. The research reached the most important conclusions that disclosing the transactions of related parties, especially the essential transactions of members of the Board of Directors, executive administrators, and major shareholders in the auditor’s report, helps to enhance confidence in investment in the economic entity. The most important recommendations were the necessity of developing the content of the audit report in disclosing related parties, because of its impact on increasing the percentage of responsibilities incurred by the auditor, as well as its impact on rationalizing investment decisions and on decision makers in the economic entity.